URGENSI KOMPETENSI GURU DALAM PENGUKURAN DAN PENILAIAN BAHASA ARAB DI SDTQ AL-MUJAHIDIN BANYUANYAR - Nur Azizah, Annisa; Audsar Ridwan Fauzi; Aldinda Fauziah; Abdul Latif Nur Rohman; Muhammad Rizki Sutolaksana (CV. Kalimasada Group, 2024)
Teacher competence in the assessment and evaluation of the Arabic language plays a crucial role in ensuring effective learning outcomes. This study highlights the significance of teacher competence in the context of measuring and evaluating Arabic language proficiency. Competent teachers are essential in designing and implementing assessment strategies that accurately gauge students' language skills and progress. Effective assessment and evaluation practices are vital for monitoring students' development and providing targeted support to enhance their language proficiency. Teachers with strong competence in assessment are able to create meaningful assessment tasks, provide constructive feedback, and make informed decisions about students' learning needs. Furthermore, teacher competence in assessment and evaluation contributes to the overall quality of Arabic language instruction, fostering a conducive learning environment that promotes language acquisition and proficiency. Continuous professional development and training opportunities are essential for enhancing teacher competence in assessment and evaluation, ultimately benefiting students' language learning experiences. In conclusion, the urgency of teacher competence in the assessment and evaluation of the Arabic language cannot be overstated. Competent teachers play a pivotal role in driving student success and fostering a culture of continuous improvement in Arabic language education.